Pengembangan Media Komik Digital Berbahasa Jerman Cerita Rakyat Batak Toba Raja Si Opat Ama dengan Bantuan Aplikasi Next G-Toon - Saruksuk, Wiwik Maywan; Simamora, Christy Aprilia; Siregar, Chyntia Pamela; Pasaribu, Novyar Ardhana; Naswa, Laili Insyirah; Hutagalung, Surya Masniari (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop German-language digital comic media that elevates the Toba Batak folklore "Si Raja Opat Ama" using the Next G-Toon application. The research method used a quantitative descriptive approach, including data collection through an online survey to assess the level of reader satisfaction with digital comics and data collection related to Toba Batak folklore from various sources. The results showed high interest from readers in digital comics, with the majority positively assessing quality, safety, ease of use, and providing recommendations for this digital comic. Visualization of the story through images and German text facilitates understanding of context and sentence structure. In conclusion, the German-language digital comic about Toba Batak folklore proved to be interesting and effective in helping learn German and understand local culture. It is recommended to develop further digital comics that raise folklore or other local cultures as an effort to preserve cultural heritage and promote Indonesia's cultural wealth